Rare, tropical and subtropical fishes in Aotearoa New Zealand : monitoring occurrences and predicting impacts : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University, Albany, New Zealand - Littlewood, Katie (Massey University, 2022)
Species redistribution due to climate change is occurring four times faster in the ocean than on land. As global temperatures rise, equatorial regions are becoming increasingly inhospitable, driving tropical and subtropical species to track favourable conditions poleward or at deeper depths, to keep within their thermal tolerances. The expectation is that tropical regions will become more inhospitable and temperate regions will become increasingly tropicalised as the ability for warmer water species to persist increases. Tracking range-shifts in the ocean is a difficult, time consuming and often expensive task, as many marine species are highly mobile, cryptic and wide ranging. As such, our understanding of climate induced distributional changes and the threats they pose is far from complete. Nevertheless, the increase of tropical and subtropical species in temperate regions has the potential to alter biodiversity, displace endemic species and cause significant shifts in ecosystem function. While Aotearoa New Zealand has remained relatively unimpacted by climate change to date, the frequency of tropical and subtropical arrivals will continue to increase as global climate change forces species to seek refuge in temperate regions. With a high level of endemism and a relatively depauperate ecosystem, the establishment of range-extending species in Aotearoa New Zealand has the potential to have negative impacts. This thesis contributes to the understanding of tropical, subtropical and rare marine fishes in Aotearoa New Zealand by highlighting the potential for citizen science as a means of monitoring occurrences, and through examining the morphology and ecological niches of arriving fishes to predict their potential impacts on Aotearoa New Zealand’s native and resident species. First, through structured questionnaires, I demonstrate that citizen scientists can provide reliable (83.33% of questionnaires) observations of tropical and subtropical fishes without the need for photographic equipment or post-hoc validation, thus providing more equitable opportunities for citizens to contribute to marine science and monitoring initiatives. Second, through analysing the broadscale trophic niche, habitat preference and morphology of marine fishes I reveal there is considerable niche overlap between arriving marine fishes and native resident marine fishes (74.37%) suggesting there is high potential for competition should arriving species establish and increase in abundance in Aotearoa New Zealand. Overall, my results highlight the need for proactive monitoring of arriving fishes, to limit the potential impacts on native and resident species and our marine ecosystems.
Keywords: 310301 Behavioural ecology